2020
DOI: 10.1186/s13033-020-00408-0
|View full text |Cite
|
Sign up to set email alerts
|

Depression and experience of incarceration in North Central Nigeria: a situation analysis at Makurdi medium security prison

Abstract: Background Human rights watchdogs have described conditions in Nigerian correctional facilities and detention centers as damaging to the physical and mental health of inmates. While the prevalence of mental disorders is high, access to appropriate healthcare is grossly inadequate. Understanding the current state of prison inmates’ mental health and well-being is an essential first step to addressing this important issue. This study aims to document the mental health and experiences of incarceration of inmates … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Wolff et al (2016), in particular, attributed the increase in self-harm in Switzerland prisons to the struggle over scarce resources. A sub-Saharan African study by Nwefoh et al (2020) attributed the high rate of depression among persons in custody to the poor conditions in the Nigerian prison. The current study has reported similar events, even though it did not set out to measure the relationship between overcrowding and suicide ideation, as well as other mental health conditions, the emotional and psychological consequences of prison congestion if not identified and managed could negatively impact on the mental health of people who live and work in the prison.…”
Section: Discussionmentioning
confidence: 99%
“…Wolff et al (2016), in particular, attributed the increase in self-harm in Switzerland prisons to the struggle over scarce resources. A sub-Saharan African study by Nwefoh et al (2020) attributed the high rate of depression among persons in custody to the poor conditions in the Nigerian prison. The current study has reported similar events, even though it did not set out to measure the relationship between overcrowding and suicide ideation, as well as other mental health conditions, the emotional and psychological consequences of prison congestion if not identified and managed could negatively impact on the mental health of people who live and work in the prison.…”
Section: Discussionmentioning
confidence: 99%
“…planning. They must be more actively engaged in obtaining the budgetary and legislative commitments to achieve this objective [47][48][49]. 4.…”
Section: The Most Important Actors In the Responses (Including Missin...mentioning
confidence: 99%
“…In a 2020 study conducted in Nigeria, 381 randomly selected people who were incarcerated completed a structured questionnaire regarding their experiences in prison as well as the Patient Health Questionnaire-9, a screening tool for depression. The study found a positive depression screen rate of approximately 38%, whereas the prison authorities had identified a depression prevalence rate of 7% among study participants (Nwefoh et al, 2020). A handful of those with depression ( n = 27) were receiving professional counseling while in prison (Nwefoh et al, 2020).…”
mentioning
confidence: 99%
“…The study found a positive depression screen rate of approximately 38%, whereas the prison authorities had identified a depression prevalence rate of 7% among study participants (Nwefoh et al, 2020). A handful of those with depression ( n = 27) were receiving professional counseling while in prison (Nwefoh et al, 2020). Approximately 52% of participants reported being dissatisfied with the prison healthcare system.…”
mentioning
confidence: 99%
See 1 more Smart Citation